DISTANCE LEARNING PRACTICAL COURSE «3D GRAPHICS»: CHALLENGES AND PROSPECTS FOR IMPLEMENTATION - Pavlova, Natalia; Dubych, Kateryna (Physical and Mathematical Education, 2025)
Formulation of the problem. Future computer science teachers and IT specialists studying at higher education institutions must acquire competencies that reveal their ability and readiness to effectively use computer graphics tools in their profession. It is advisable to include educational components in the content of educational and professional programs, the study of which is aimed at developing skills in working with three-dimensional graphics, modelling, animation and design tools. The implementation of an activity-based approach in combination with the updating of software tools necessitates the development of a distance learning course as a practice-oriented resource. Materials and methods. Analysis of scientific and methodological works on computer graphics; identification of key recommendations for the development and implementation of a distance learning course as a practice-oriented resource; observation, questioning, and presentation of personal teaching experience. Results. Ways to overcome the main challenges in studying 3D graphics are proposed, and individual aspects of developing and implementing a distance practice-oriented course that combines instructional, informational, control, and communicative components are analyzed. The course modules are presented as a system of laboratory (practical) classes, each of which contains: task formulation, instructional materials, an activity part, and a final reflection. Visualization of the survey results and generalization of our own pedagogical experience enabled us to identify the challenges and prospects of implementing a distance learning course in the professional training of future specialists. Conclusions. The key challenges of the educational process are issues of technical and software support, adherence to the principles of an individual and differentiated approach, and the introduction of active and practice-oriented learning. The training modules of the distance learning course comprise a set of laboratory (practical) works that contain variable, competence-based tasks of a professional nature. The effectiveness of the educational process is enhanced by the use of BYOD technology. Learning the Blender 3D software environment is advisable given its versatility, accessibility, and advantages in the process of working with it.